Geographic Proximity and Racial Disparities in Cancer Clinical Trial Participation - Kanarek, Norma F. (2010)
This study assessed the effects of race and place of residence on clinical trial participation by patients seen at a designated NCI comprehensive cancer center. Clinical trial accrual to cancer case ratios were evaluated using a database of residents at the continental United States seen at The Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins from 2005 to 2007. Place of residence was categorized into 3 nonoverlapping geographic areas: Baltimore City, non–Baltimore City catchment area, and non–catchment area. Controlling for age, sex, county poverty level, and cancer site, significant race and place of residence differences were seen in therapeutic or nontherapeutic clinical trials participation. White non–Baltimore City catchment area residents, the designated reference group, achieved the highest participation rate. Although the test of interaction (control group compared with all others) was not significant, some race–geographic area group differences were detected. In therapeutic trials, most race–place of residence group levels were statistically lower and different from reference; in nontherapeutic trials, race-specific Baltimore City groups participated at levels similar to reference. Baltimore City residents had lower participation rates only in therapeutic trials, irrespective of race. County poverty level was not significant but was retained as a confounder. Place of residence and race were found to be significant predictors of participation in therapeutic and nontherapeutic clinical trials, although patterns differed somewhat between therapeutic and nontherapeutic trials. Clinical trial accruals are not uniform across age, sex, race, place of residence, cancer site, or trial type, underscoring that cancer centers must better understand their source patients to enhance clinical trial participation.